L’enseignement des langues et cultures étrangères à l’école primaire : un exemple d’utilisation de document authentique multimédia - Marie-Ange Dat; Nathalie Spanghero-Gaillard (Corela)
Teaching/learning of a foreign language in primary schools depends on methodology, teaching skills material and teaching practices, even though there is a strong political will to establish this discipline. At the beginning of the 2002/2003 school year, we launched a series of activities in foreign language courses (English and Spanish) based on part of a multimedia magazine featuring “languages the fun way”. These classroom observations and exercises performed by semi-autonomous pupils were carried out in a number of primary schools in Toulouse and its surroundings as part of a project financed by the Midi-Pyrenees regional council. First of all we will present the key points of the announcements made by the successive French National Education Ministries ever since the need to implement the teaching/learning of foreign languages in primary schools was taken into account. We will point to the educational system's evident shortcomings, which make it difficult to achieve teaching practice's that meet the Ministry's expectations. Finally, we will present a way to use an electronic magazine, demonstrating how it could represent teaching material that is compatible with the learning goals set forth by the Ministry, using active methods in which the learner is involved. We will insist in particular about the importance of three related factors: pupil's learning strategies, teaching approach and conception of material for educational software.